495 RECURRENT SPONTANEOUS PNEUMOTHORAX ASSOCIATED WITH NONINVASIVE POSITIVE PRESSURE VENTILATION IN A PATIENT WITH DUCHENNE MUSCULAR DYSTROPHY. (1st January 2006) - De Jesus-Monge, W. E.; Santos, G.; Laureano, A. F.; Borri-Sola, C.; Sepulveda, V.
Abstract : Introduction: Duchenne muscular dystrophy (DMD) results in progressive loss of respiratory muscle strength and death from respiratory insufficiency. A therapy to avoid these respiratory complications in these patients is noninvasive positive pressure ventilation (NIPPV). Spontaneous pneumothorax is the presence of air in the pleural space in the absence of thoracic trauma and it has been rarely reported among patients on chronic, intermittent NIPPV with and without DMD. Purpose: To discuss the clinical presentation and management of recurrent spontaneous pneumothorax associated with NIPPV in patients with DMD and the indications and use of NIPPV in these patients by presentation of a case. Case Report: A 31-year-old man with a medical history of DMD, chronic respiratory failure on NIPPV at nighttime, and allergic rhinitis presented with an apical left pneumothorax by routine chest x-ray for follow-up visits to the Pulmonary Medicine Clinic for three separate episodes over a 12-week period. He had a right pneumothorax previously 8 years before this period. During multiple hospitalizations for pneumothorax management, he received supplemental oxygen therapy, thoracostomy tube placement for percutaneous aspiration, and doxycycline pleurodesis, resulting in lung reexpansion. On the last hospitalization the patient refused further management after being thoroughly oriented. Discussion: Patients with DMD have increased risk for sleep-disordered breathing. Long-term NIPPV is effective for improving the quality of life and survival of neuromuscular disease patients, especially with DMD. Serial evaluation and adjustment of NIPPV are necessary because patients' requirements change with time. Conclusion: Since chronic NIPPV is widely used, patients and caregivers must be aware of the occurrence of spontaneous pneumothorax as a complication of NIPPV in DMD.